Coupling of molecular vibration and metasurface modes for efficient mid-infrared emission. Issue 2 (20th December 2021) - Nishijima, Yoshiaki; Morimoto, Shinya; Balčytis, Armandas; Hashizume, Tomoki; Matsubara, Ryosuke; Kubono, Atsushi; To, Naoki; Ryu, Meguya; Morikawa, Junko; Juodkazis, Saulius
Abstract : We demonstrate extraordinarily spectrally selective narrowband mid-infrared radiation via coupling of plasmon resonance and molecular vibration. Absorbance and thermal emittance with resonant peak FWHM ≤ 124 nm at λ = 5.73 μm, corresponding to a Q -factor of ∼92.3 were obtained. Abstract : We demonstrate extraordinarily spectrally selective narrowband mid-infrared radiation absorbance and thermal emittance with resonant peak FWHM ≤ 124 nm at λ = 5.73 μm, corresponding to a Q -factor of ∼92.3. This was achieved by harnessing mode coupling between a plasmonic metal–insulator–metal (MIM) metasurface and molecular vibrational mode resonances, with coupling efficiency ranging from η ∼ 3.9% to 6.6%. In addition, thermal radiation emissivity is in close accordance to the metamaterial absorbance spectrum, as described by Kirchhoff's law of thermal radiation, and furthermore, emission was not angle dependent, unlike that exhibited by grating-based emitters. The experimentally investigated MIM structures remained stable up to a 250 °C heating temperature. MIM metamaterials with strong and spectrally tailored vibrational coupling behaviors represent a new paradigm in photo-thermal energy conversion. The experimentally observed pronounced resonant coupling behaviour was well described by finite-difference time-domain simulations of the plasmonic structure, where molecular vibration contributions were modeled using the Lorenz oscillator approximation.